Strategies in the Surgical Management of Atrial Fibrillation - Leanne Harling; Thanos Athanasiou; Hutan Ashrafian; Justin Nowell; Antonios Kourliouros (Cardiology Research and Practice)
Atrial fibrillation (AF) is associated with substantial morbidity, mortality, and economic burden and confers a lifetime risk of up to 25%. Current medical management involves thromboembolism prevention, rate, and rhythm control. An increased understanding of AF pathophysiology has led to enhanced pharmacological and medical therapies; however this is often limited by toxicity, variable symptom control, and inability to modulate the atrial substrate. Surgical AF ablation has been available since the original description of the Cox Maze procedure, either as a standalone or concomitant intervention. Advances in novel energy delivery systems have allowed the development of less technically demanding procedures potentially eliminating the need for median sternotomy and cardiopulmonary bypass. Variations in the definition, duration, and reporting of AF have produced methodological limitations impacting on the validity of interstudy comparisons. Standardization of these parameters may, in future, allow us to further evaluate clinical endpoints and establish the efficacy of these techniques.